X-ray Tomographic Imaging of Tensile Deformation Modes of Electrospun Biodegradable Polyester Fibers - Maksimcuka, Jekaterina; Obata, Akiko; Sampson, William W.; Blanc, Remi; Gao, Chunxia; Withers, Philip J.; Tsigkou, Olga; Kasuga, Toshihiro; Lee, Peter D.; Poologasundarampillai, Gowsihan (Frontiers in Materials, 2017)
Electrospinning allows the production of fibrous networks for tissue engineering, drug delivery and wound healing in healthcare. It enables the production of constructs with large surface area and a fibrous morphology that closely resembles the extracellular matrix of many tissues. A fibrous structure not only promotes cell attachment and tissue formation, but could also lead to very interesting mechanical properties. Poly(3-hydroxybutyrate-co-4-hydroxybutyrate) (P(3HB-co-4HB)) is a biodegradable polyester that exhibits large (>400%) elongation before failure. In this study, synchrotron X-ray phase contrast imaging was performed during tensile deformation to failure on a non-woven fibre mat of P(3HB-co-4HB) fibres. Significant reorientation of the fibres in straining direction was observed, followed by localised necking and eventual failure. From an original average fibre diameter of 4.3 μm a bimodal distribution of fibre diameter (modal diameters of 1.9 and 3.7 μm) formed after tensile deformation. Extensive localised necking (thinning) of fibres between (thicker) fibre-fibre contacts was found to be the cause for non-uniform thinning of the fibres, a phenomenon that is expected, but has not been observed in 3D previously. The data presented here has implications not only in tissue regeneration but for fibrous materials in general.